Treatment of bone tumors in the femoral trochanteric area. - Apichat Asavamongkolgul (2018)
To report the management of bone tumor in the femoral trochanteric area in terms of safety,functional outcome and patient satisfaction. Thirty-eight patients with impending or pathological fracture at the trochanteric region of the femur were treated surgically at the Department of Orthopaedic Surgery, Faculty of Medicine Siriraj Hospital from 1998 to 2007. Thirteen males and 25 females with a mean age of 49.7 years, 11 patients had benign bone tumors (5 fibrous dysplasia, 3 chondroblastoma and 1 each of aneurysmal bone cyst, bone island and intraosseous hemangioma). Twenty-seven patients had metastatic lesions (10 breast, 3 lung, 2 hepatocellular, 2 colon, 2 prostate and 1 each of multiple myeloma, gastric, cervix, thyroid, nasopharynx, bladder, secondary sarcoma and of unknown origin). Twenty-six patients presented an impending fracture and the remainder had a pathological fracture. All patients were treated with curettage in conjunction with a sliding hip compression screw and plate, except one patient with bone deformity from fibrous dysplasia who had an adjunct valgus osteotomy. Eleven patients were augmented with bone grafting, 19 with bone cement and 8 patients had no augmentation. The mean follow-up time was 3 years. The mean operative time and estimated blood loss was 98 minutes and 542 ml respectively. Two complications were found in this series and successfully managed. There was no serious intra or perioperative complication. The mean functional score was 79.5 percent in metastatic group and 89.7 percent in benign bone group. In the present study, the outcomes of intralesional curettage and stabilization with a sliding hip compression screw and plate for bone tumors in the femoral trachanteric area were safe and only 2 treatable complications were found. Most patients had less pain after the operation and could ambulate independently with gait support and all satisfied with the results.